2004
DOI: 10.1097/00024720-200406000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Thoracic Pedicle Screw Placement Using Fluoroscopic Imaging

Abstract: Guided by intraoperative fluoroscopic imaging and anatomic landmarks, thoracic pedicle screws can be placed safely. Early clinical follow-up reveals excellent results with minimal loss of kyphosis correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…In a study of Guzey et al [16], the rate of misplacement was 20.3 % for 113 upper and middle thoracic screws placed under uniplanar or biplanar fluoroscopy. An in vivo study of non-deformed spines reported on 27 and 109 screws placed at T1-T2 and between T3 and T9, respectively, from a total of 209 screws placed between T1 and T12 [22]. With fluoroscopy support, the placement accuracy was 88 % for the T1-T2 screws (15 screws solely contained in the pedicle and 9 lateral perforations less than 4 mm), and 66 % for the T3-T9 screws (15 screws completely intrapedicular, 55 lateral perforations less than 4 mm).…”
Section: Accuracy Of Placement: Thoracic Spinementioning
confidence: 99%
“…In a study of Guzey et al [16], the rate of misplacement was 20.3 % for 113 upper and middle thoracic screws placed under uniplanar or biplanar fluoroscopy. An in vivo study of non-deformed spines reported on 27 and 109 screws placed at T1-T2 and between T3 and T9, respectively, from a total of 209 screws placed between T1 and T12 [22]. With fluoroscopy support, the placement accuracy was 88 % for the T1-T2 screws (15 screws solely contained in the pedicle and 9 lateral perforations less than 4 mm), and 66 % for the T3-T9 screws (15 screws completely intrapedicular, 55 lateral perforations less than 4 mm).…”
Section: Accuracy Of Placement: Thoracic Spinementioning
confidence: 99%
“…Seven studies had different patient groups with alternative treatment options. [2][3][4][5][6][7][8]10,11,16,20,21,[24][25][26][29][30][31][32][33][34][35][36]38,43,44,47,48,51,52,54,55,57,58,[62][63][64][65] Thirteen studies were prospective, 25 were retrospective, and 1 study was both pro-and retrospective. 3 Seventeen studies reported a follow-up (mean follow-up 19.0 months, range 1-118 months).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted however, this placement accuracy reported does include some deformity cases in the final statistic. An in vivo study of non-deformed spines [11] reported on 27 and 109 screws placed at T1-T2 and between T3 and T9, respectively, from a total of 209 placed between T1 and T12. The use of fluoroscopy was employed which resulted in an approximate placement accuracy of 56% for the T1-T2 screws, and 14% for the T3-T9 screws.…”
Section: Discussionmentioning
confidence: 99%